A case of nodular episcleritis mimicking a solitary giant episcleral mass. Issue 2 (March 2023) - Zhou, Lan; Wang, Juanjuan; Xu, Guihua; Wang, Dingding; Wang, Xiaoyi; Chen, Zilin
Purpose: To describe an atypical nodular episcleritis mimicking a solitary giant episcleral mass, which is not attributed to any systemic diseases and identified only after immunohistochemical examination. Case report: A sixty-year-old Chinese woman with systemic hypertension presented with 6-month history of giant, solitary and redness epibulbar mass arising from the superior aspect of her left eye. The lesion gradually enlarged, even with 6-month history of irregular topical steroid eye drops treatment. Imaging studies and laboratory test revealed a 10 mm × 8 mm episcleral mass absence of any infection indicator and autoimmune antibody changes. The mass was completely removed before its extension through the deep scleral, histopathologic examination revealed a nodular episcleritis composed of various chronic inflammatory cells infiltration. Topical steroid eye drops treatment combined with oral steroidal anti-inflammatory drugs was then administrated regularly for 1 month, and no recurrence occurred after 1-year follow-up. Conclusion: Nodular anterior episcleritis is characterized by underlying chronic inflammation of the anterior episclera and can be presented as asymptomatic episcleral mass. Besides a thorough investigation systemically, tissue biopsy is required for definite diagnosis.